Family-Member Variant of Directory Observed Therapy Short Course (DOTS) in Current Pulmonary Tuberculosis (PTB) Management: A Way Out in Resource-Constrained Settings – A Case Report - Terhemen Joseph Igbudu; Livinus Egwuda; Tsav Peter Mbaave (International Journal of Medical Research, 2015)
Appreciation of patients’ family dynamics may be very crucial in deciding the appropriate treatment option aimed at reducing treatment failures and drug resistance in the management of pulmonary tuberculosis especially in the resource-constrained settings. We reported a case of a 62 year old retiree with pulmonary tuberculosis who had financial challenges and was successfully treated using the family-member variant of DOTS. This modality of treatment was easily accepted and eventually addressed some of the financial challenges the patient had. Family-member variant of DOTS was successfully demonstrated in the management of PTB and was seen to have reduced the variable cost of treatment, distortion of family dynamics and enhanced family harmony.